2004
DOI: 10.1111/j.1600-9657.2004.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Federal University of Santa Catarina follow‐up management routine for traumatized primary teeth – part 1

Abstract: The objective of this study was to verify if the follow-up management routine of traumatized primary teeth set up by Federal University of Santa Catarina, which performs clinical and radiographic assessments (15 and 45 days; 4, 8 and 12 months) after the oral trauma, enabled an early diagnosis of sequelae which would indicate the need for endodontic intervention, as well as the influence a type of trauma and the child's age could have in the severity of the sequelae. In this study 52 sets of records were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 5 publications
2
37
0
12
Order By: Relevance
“…However, a darkened tooth should be diagnosed as necrotic only when associated with abscess, swelling, and pathological periapical lesion resorption. 16,17,18 Cardoso, and Rocha 19 showed that among the teeth diagnosed with pulp necrosis and discoloration, 66.7% were grayish and 22.2% were yellowed. Discoloration is an important but not decisive factor in the diagnosis of pulp necrosis in traumatized primary teeth.…”
Section: Discussionmentioning
confidence: 99%
“…However, a darkened tooth should be diagnosed as necrotic only when associated with abscess, swelling, and pathological periapical lesion resorption. 16,17,18 Cardoso, and Rocha 19 showed that among the teeth diagnosed with pulp necrosis and discoloration, 66.7% were grayish and 22.2% were yellowed. Discoloration is an important but not decisive factor in the diagnosis of pulp necrosis in traumatized primary teeth.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,4,5,6 The most common age group in which primary tooth injury occurs is 1 to 3 years. 7 Nonetheless, Osuji et al 8 (1996) states that children aged 4 to 5 years are the most likely to suffer trauma. However, the current literature is unanimous in that trauma occurs as a result of psychomotor underdevelopment and poor motor skills, which do not allow the child to perform precise and safe movements.…”
Section: Introductionmentioning
confidence: 99%
“…A descoloração coronária é um dos tipos de seqüelas mais observadas após traumatismos dentários com uma freqüência variando de 25 a 63% (BORUM; ANDREASEN, 1998;ROCHA, 2004;ERICKSON, 1995;HOLAM;RAM, 1999;KENWOOD;SEOW, 1989). Pesquisas também mostram serem uma das primeiras seqüelas clinicamente visíveis logo após o trauma (CARDOSO; ROCHA, 2004;KENWOOD;SEOW, 1989), podendo ser do tipo transitória ou permanente e apresentar diferentes tonalidades (LEVINE, 1982).…”
Section: Revisão De Literaturaunclassified
“…Pesquisas também mostram serem uma das primeiras seqüelas clinicamente visíveis logo após o trauma (CARDOSO; ROCHA, 2004;KENWOOD;SEOW, 1989), podendo ser do tipo transitória ou permanente e apresentar diferentes tonalidades (LEVINE, 1982). A coloração para o amarelo geralmente está relacionada à obliteração do canal pulpar e os tons cinza ou azulado podem indicar a necrose pulpar (BENNET, 1964;HOLAN;FUKS, 1996;JACOBSEN;SANGNES, 1978).…”
Section: Revisão De Literaturaunclassified
See 1 more Smart Citation